Major histocompatibility complex class II antigen expression in B and T cell non-Hodgkin's lymphoma. Issue 1 (January 1987) - Smith, M E; Holgate, C S; Williamson, J M; Grigor, I; Quirke, P; Bird, C C
Abstract : An immunohistochemical study of 46 B and T cell non-Hodgkin's lymphomas, using monoclonal antibodies to the products of the major histocompatibility complex (MHC) class II antigen subregions, DP, DQ, and DR, showed that most B and T cell lymphomas express these antigens. Both coordinate and non-coordinate expression of MHC class II antigens was observed, but this did not correlate with immunological phenotype, morphological grade, or proliferation index as determined by flow cytometry.